Can Health Human Capital Help the Sub-Saharan Africa Out of the Poverty Trap? An ARDL Model Approach - Wang, Qiu-Su; Hua, Yu-Fei; Tao, Ran; Moldovan, Nicoleta-Claudia (Frontiers in Public Health, 2021)
This paper explores that impact of health human capital on the poverty trap in Sub-Saharan Africa by ARDL model. In the long run, there is no evidence that health human capital can help the Sahara out of the poverty trap. While health human capital has a significant effect on poverty reduction in the short term. There is a threshold effect in the poverty reduction model of healthy human capital. When the economic development level reaches the threshold, the effect of poverty reduction is more obvious and deeper. The extended Solow economic growth model also proved out that if the external human capital breaks through the threshold, it can make developing countries get rid of the poverty trap. Therefore, the economic development brought about by health care expenditure must benefit the poor in Sub-Saharan Africa, and allow them to enjoy the welfare of social security.